Meanings and mobilizations: a cultutal Politics approach to social movements and states - Rubin, Jeffrey W.
Though examination of the Zapotec movement in Juchitán, México, the Zapatistas in Chiapas, Pan-Maya movements in Guatemala, and the Afro-Reggae Cultural Group in Río de Janeiro, This article will show that social movements are best analyzed througa combined focus on the circuitours historial pathways of their origins and emergence and on the diverse pieces of representation and meaning out of which they are made